Marine Bacteria Community in a 150-m Depth Tachai Island, the Southeast Andaman Sea of Thailand - Sripan, Donlaporn; Wilantho, Alisa; Khitmoh, Khunnalack; Wongsawaeng, Doonyapong; Ouazzani, Jamal; Chavanich, Suchana; Tongsima, Sissades; Somboonna, Naraporn (Frontiers in Marine Science, 2021)
The southeast Andaman Sea 52-m off the west coast of Phang Nga province, Thailand, is located in the Indian Ocean, representing a hotspot for marine biodiversity of the world. This study utilized metagenomics combined 16S rRNA gene (V3–V4) sequencing, and firstly revealed the microbiota and their metabolism potentials of this site at an epipelagic depth (150-m depth, TC150M), including comparison with its pelagic depth (30-m depth, TC30M) as well as other nearby Thailand and global ocean sites. Between TC150M and TC30M, the TC150M microbial metagenomics was an eight-fold higher, and the microbiota comprised, for examples more abundant Bacteroidetes while fewer Proteobacteria, than the TC30M. The microbial metabolic potentials of the TC150M were statistically higher in replication repair and metabolisms of amino acids, lipids, nucleotides, and xenobiotics biodegradation, etc. Following comparative microbiota analyses between three Andaman Sea sites and two Gulf of Thailand sites, the relatively great proportions of Bacteroidetes, Nitrospirae, Gemmatimonadetes, and Chlorobi characterized the southeast Andaman Sea. Nevertheless, the microbiota representing Thailand marine sites remained distinguished from the global ocean sites where beta diversities were close. Thai maritime sites showed proportionally higher Proteobacteria, Bacteroides, Nitrospirae, Gemmatimonadetes, and Chlorobi. Thus, the Thai marine microbiota database helps better understand our global ocean microbiota and microbial metabolic potentials. Here, the microbial metabolism potentials between Thailand and the global ocean sites of relatively close microbiota databases encompose the similar functions yet in statistically different frequencies. Our research provided the first preliminary marine microbiome comparison between the epipelagic and pelagic sea levels of the southeast Andaman Sea, Thailand.